Pengaruh Konsentrasi NaOH dan Suhu Delignifikasi pada Kandungan Lignoselulosa Tandan Kosong Kelapa Sawit - Permana, Hafid Andre; Delvitasari, Febrina; Hartari, Widia Rini; Maryanti, Maryanti (Politeknik Negeri Lampung, 2024)
Palm oil processing in the industry produces products and waste; the waste generated from the palm oil processing process will have a negative impact on the environment if it is not processed. Oil palm empty fruit bunches are lignocellulosic solid wastes that contain cellulose, lignin, and hemicellulose content, so they have the potential to be raw materials for making bioethanol. In the process of producing bioethanol, delignification is an early stage that aims to reduce the lignin content in lignocellulosic materials with alkaline or alkaline pretreatment solutions such as the use of NaOH can be used to help separate lignin from cellulose fibers. This study aimed to analyze the effect of NaOH concentration and delignification temperature on the lignocellulosic content of oil palm empty fruit bunches. The research method was arranged descriptively with two treatments: the concentration of NaOH consisting of 3%, 4%, and 5%, and the heating temperature consisting of 100 oC, 110 oC, and 120 oC. Lignocellulosic content can be calculated using the Chesson method analysis with the Microsoft Excel 2016 application as a data processor. The results showed that 1 M NaOH concentration with heating temperature had an effect on the observations of hemicellulose, cellulose, and lignin. The best treatment of 1 M NaOH concentration and heating temperature on hemicellulose, cellulose, and lignin was produced by the treatment of 5% NaOH concentration with a heating temperature of 120 0C.